The Influence of Incentives and Health Insurance on Teacher Performance at Islamic Elementary School - Yuliaty, Farida; Kokasih, Kokasih; Harahap, Linda Rahmadhani; Wibisono, Fallery Setyaprawira; Rifal, Dwiki Indar; Amin, Nadia Arsita Usman (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study examines the impact of incentives and health insurance on teacher performance at Annurilah Islamic Elementary School located in Pantai Labu District, Deli Serdang Regency, North Sumatra. The research was motivated by teacher dissatisfaction with the current profit-sharing incentive system and unequal health insurance coverage. The study's purpose is to analyze how these factors influence teacher motivation and performance, identify the problems with the school's current systems, and provide recommendations for improvement. Using a quantitative approach with an associative-causal research design, the study collected primary data from all 33 teachers at the school via questionnaires. A simple linear regression analysis was used to test the hypothesis. The findings indicate that both incentives and health insurance have a significant and positive influence on teacher performance. However, the study also found that the school's ineffective and unfair system, which includes a non-transparent profit-sharing model for incentives and unequal health insurance coverage, can lead to dissatisfaction and negatively affect performance. The research suggests that while these factors can improve performance, their current implementation at the school hinders their effectiveness.